The struggle for power and influence in the city of Aleppo between (1184 -1226 AH /1770 -1811 AD) - عثمان, ربيع (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research deals with the political struggles over power and influence in the city of Aleppo at the end of the eighteenth century and the beginning of the nineteenth century , at that stage , Aleppo witnessed a bloody struggle for power and influence between the various forces present in the city's political arena . At the head of those forces were the Ottoman governor , the legitimate representatives of the ottoman central authority in the state , and the supervision , who are considered among the important social groups that played an important role in the political , economic and social life in the province of Aleppo at that important historical stage . The supervision at that stage formed the main local force that stood in the face of the Ottoman force represented by the Ottoman governor and soldiers . The Janissaries also played a major role in those conflicts, as their strength increased during the research period , and they main political and military forces in the city . A group of internal factors related to the general situation in Aleppo and external factors related to the general situation in the Ottoman Empire came together . These factors contributed to the emergence and escalation of local influence in the Ottoman states at the expense of the decline of the central authority , including the city of Aleppo, which was known as a stage of security chaos and political conflicts between the years 1184-1226AH/ 1770-1811AD.